(untitled) (International Journal of Social Research & Innovation, 2018)
Supply chain management (SCM) practices have become a key determinant of competitive advantage of business enterprises. Effectively carried out supply chain management practices provide a strategic improvement to supply chain performance and thereby increases the performance of companies. The present study examines the dimensions of supply chain management components (practices, competences, and concerns) and their relationship to supply chain performance. Data was collected from 250 medium and small enterprises of Madurai District in Tamil Nadu, between December 2016 and July 2017. The enterprises were selected using simple random sampling. The relationship between supply chain management components and supply chain performance was investigated using structural equation modeling. The resulting model indicated that supply chain management practices, competence, and concerns have a direct, positive impact on supply chain performance. Recommendations for improving operational capability are provided accordingly.